2019
DOI: 10.1038/s41598-019-49868-6
|View full text |Cite
|
Sign up to set email alerts
|

CPT1A plays a key role in the development and treatment of multiple sclerosis and experimental autoimmune encephalomyelitis

Abstract: Human mutations in carnitine palmitoyl transferase 1A (CPT1A) are correlated with a remarkably low prevalence of multiple sclerosis (MS) in Inuits (P479L) and Hutterites (G710E). To elucidate the role of CPT1A, we established a Cpt1a P479L mouse strain and evaluated its sensitivity to experimental autoimmune encephalomyelitis (EAE) induction. Since CPT1a is a key molecule in lipid metabolism, we compared the effects of a high-fat diet (HFD) and normal diet (ND) on disease progression. The disease severity incr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
39
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 18 publications
(42 citation statements)
references
References 49 publications
3
39
0
Order By: Relevance
“…Here, we have presented that MS, ALS, and PD are characterized by local, and systemic changes in metabolism. Based on a CPT1A mutation found in the Inuit population, which seems to confer resistance to neurodegeneration by reducing CPT1A activity by 78%, we decided to test the effect of CPT1A de-activation in neurodegeneration in two ways: by pharmacologically blocking CPT1, and by creating a new Cpt1a p479l mice 26 . The findings from this study revealed that the Cpt1a-mutated mice are resistant to the development of not only EAE, but also PD and to some extent ALS.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…Here, we have presented that MS, ALS, and PD are characterized by local, and systemic changes in metabolism. Based on a CPT1A mutation found in the Inuit population, which seems to confer resistance to neurodegeneration by reducing CPT1A activity by 78%, we decided to test the effect of CPT1A de-activation in neurodegeneration in two ways: by pharmacologically blocking CPT1, and by creating a new Cpt1a p479l mice 26 . The findings from this study revealed that the Cpt1a-mutated mice are resistant to the development of not only EAE, but also PD and to some extent ALS.…”
Section: Discussionmentioning
confidence: 99%
“…To examine the role of CPT1A activity, a mouse line (B6J-Cpt1a < em1Nki >) expressing the Inuit mutant allele Cpt1a P479L (Cpt1a < em1Nki > , MGI number: 5810634) was generated and genotyped as previously described 26 .…”
Section: Generation Of Cpt1a P479l Micementioning
confidence: 99%
See 3 more Smart Citations